Kinerja keuangan perusahaan asuransi jiwa di Indonesia berdasarkan tingkat profitabilitas - Febriyanti, Laksmita; Ananda Raf’i, Muhammad; Darmawan, Rahmat Dimas; Kurnia, Robby; Hanggraeni, Dewi (Jurnal Paradigma Ekonomika, 2021)
This study investigates the main determinants of the profitability of life insurance companies in Indonesia. It examines the relationship between the profitability of insurance companies, namely investment income, underwriting profit, and overall net profit. The annual financial reports of ten life insurance companies in Indonesia covering ten years (2010-2019) were sampled and analyzed through panel regression. The findings indicate that gross written premium has a negative effect on overall net profit, yet a positive impact on the underwriting profit of insurance companies. Furthermore, there is a positive relationship between claim payments and the overall net profit of life insurance companies. Further research revealed a positive relationship between total assets and indicators of profitability. The policy implications of this study for insurance industry stakeholders are far-reaching. This study fulfills an urgent need to investigate issues critical to life insurance companies’ sustainability, growth, and profitability in developing countries. Â